2017
DOI: 10.1016/j.juro.2016.09.122
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Imaging Modality Effect on Surgical Management of Nephrolithiasis: A Multicenter, Randomized Clinical Trial

Abstract: Purpose: In the emergency department ultrasonography is emerging as an alternative to computerized tomography for diagnosing patients with nephrolithiasis. In this multicenter randomized clinical trial we examined rates of urological referral and intervention to elucidate whether the initial diagnostic imaging modality affected the management of nephrolithiasis. Materials and Methods: Patients 18 to 76 years old who presented to the emergency department with renal colic across 15 diverse treatment centers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…One possibility is diagnostic ultrasound performed by radiology, which is more sensitive than PoCUS. 13 However, in many centres including ours, a radiology performed ultrasound is only available at 0800 to 1600 hours, so this is not an option for patients presenting outside of this timeframe. KUB X-ray is also reasonable considering its lower radiation dose, 0.7 mSV compared to 10-12 mSV with CT and 1-3 mSV with low dose CT. 14 However, it is less sensitive and may not exclude the need for further imaging, so CT is the best available imaging modality to confirm a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is diagnostic ultrasound performed by radiology, which is more sensitive than PoCUS. 13 However, in many centres including ours, a radiology performed ultrasound is only available at 0800 to 1600 hours, so this is not an option for patients presenting outside of this timeframe. KUB X-ray is also reasonable considering its lower radiation dose, 0.7 mSV compared to 10-12 mSV with CT and 1-3 mSV with low dose CT. 14 However, it is less sensitive and may not exclude the need for further imaging, so CT is the best available imaging modality to confirm a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Der Ultraschall (US) stellt sowohl in der Notfall-als auch in der Routinediagnostik die erste Wahl dar [4]. Die sonographische Darstellung des Harntrakts ist sicher, kann den Aufenthalt in der Notaufnahme signifikant verkürzen [5] und führt zudem zu keinem relevanten Zeitverlust bis zu einer eventuellen Intervention [6,7]. Der Farbdopplerultraschall eignet sich in der akuten Kolik für die initiale Diagnose eines Harnleitersteins und ist mit den Ergebnissen des Steinsuch-CT vergleichbar [8,9].…”
Section: Ultraschallunclassified
“…A multicenter, pragmatic, comparative effectiveness trial published in 2014 randomized over 2,500 patients with suspected kidney stones to POCUS, RPUS, or CT and concluded that ultrasound (RPUS or POCUS) is a safe approach for the evaluation of ureterolithiasis, noting that "return emergency department visits, hospitalizations, and diagnostic accuracy did not differ significantly Journal of the American College of Radiology among the groups" [5]. RPUS when compared with POCUS was less likely to result in subsequent CT (27% with RPUS versus 41% with POCUS) [5,29].The study showed a small but significant longer length of emergency department stay for RPUS than either the POCUS or CT groups (7.0 hours versus 6.3 and 6.4 hours, respectively) [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…both diagnostic accuracy and patient treatment will be unchanged" [35]. A secondary analysis of the large prospective multicenter randomized trial comparing ultrasound to CT as an initial imaging modality found that there was no significant difference between timing of urologic intervention based on the initial imaging modality [29].…”
Section: Literature Reviewmentioning
confidence: 99%